Pemberitaan Problem Rumah Tangga Artis di Televisi dalam Hukum Islam dan Hukum Penyiaran di Indonesia - Ahmad Taufik Riadi; Lilik Andaryuni (CV. Creative Tugu Pena, 2024)
This research aims to find out, one, what is the best way to resolve household problems? two, how is the analysis of article 3 UURI No. 32 of 2002 regarding reporting on artists' domestic problems on television? Is normative legal research, using a juridical approach. Processing legal materials by means of inventory, identification, classification and systematization. Qualitative analysis (interpretation). and using teleological interpretation, as well as making deductive conclusions. research results, good resolution of household problems can be done by discussing, negotiating, then if it still doesn't work, you can consult psychology or a family consultation institution, don't spread problems into the public domain, and the final path that can be chosen is divorce. Showing artists' domestic problems is not in line with Law no. 32 of 2002, because it is not a show that strengthens national integration, it is not a show that fosters the character and identity of a nation of faith and piety, it is not a show that makes the life of the nation intelligent and it is not a show that advances general welfare.